Hubungan diabetes melitus dengan kejadian gagal ginjal kronik - Smith Imanuel Saputra; Khairun Nisa Berawi; Susianti Susianti; Exsa Hadibrata (CV. Jasa Sukses Abadi, 2023)
Diabetes mellitus (DM) is a group of metabolic diseases associated with increased blood glucose. Chronic hyperglycemia in diabetes mellitus contributes to the emergence of various complications in the form of damage, dysfunction and failure of various organs, one of which is the kidney. Kidney is a vital organ that plays a very important role in maintaining the stability of the environment in the body. The kidneys regulate the balance of body fluids, electrolytes and acid base by filtering blood through the kidneys, selective reabsorption of water, and excreting excess as urine and removing metabolic waste (urea, creatinine and uric acid) and foreign chemicals. Diabetic nephropathy is a degenerative kidney vascular disorder, associated with disturbances of carbohydrate metabolism or sugar intolerance (diabetes mellitus). This study aims to see the relationship between diabetes mellitus and the incidence of chronic kidney failure. Several journals have found a positive relationship between diabetes mellitus and the incidence of chronic kidney failure.